2023
DOI: 10.1111/jace.19104
|View full text |Cite
|
Sign up to set email alerts
|

Phase evolution and strong temperature‐dependent electrostrictive effect in (1−x)Pb(Mg1/3Nb2/3)O3xPbTiO3 solid solutions

Abstract: (1−x)Pb(Mg1/3Nb2/3)‐xPbTiO3 (PMN‐xPT) ceramics with x ranging from 0.1 to 0.3 were synthesized by solid‐state reaction method. X‐ray diffraction, dielectric and ferroelectric property characterizations were systematically investigated. As x rises, the PMN‐xPT transitions from a cubic to a rhombohedral phase, resulting in an enhancement in ferroelectricity. Our findings show that the electrostrain and longitudinal electrostrictive coefficient Q33 both increase and then decrease within a critical region located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…[60][61][62] Huang et al, on the other hand, recently demonstrated a strong temperaturedependent characteristic of Q 33 in PMN-xPT ceramics with the temperature around the critical region. 22 In this PMN-xPZT system, the Q 33 value of all samples exhibits a modest upward trend as temperature rises, which could be attributed to phase transition and domain reorientation reducing the Q 33 at low temperatures, whereas the Q 33 value at high temperatures is considerably closer to the intrinsic value. It can be observed that composition x = 0.4 exhibits the best temperature stability, whereas the x = 0.5 component shows the optimum electrostrictive performance.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…[60][61][62] Huang et al, on the other hand, recently demonstrated a strong temperaturedependent characteristic of Q 33 in PMN-xPT ceramics with the temperature around the critical region. 22 In this PMN-xPZT system, the Q 33 value of all samples exhibits a modest upward trend as temperature rises, which could be attributed to phase transition and domain reorientation reducing the Q 33 at low temperatures, whereas the Q 33 value at high temperatures is considerably closer to the intrinsic value. It can be observed that composition x = 0.4 exhibits the best temperature stability, whereas the x = 0.5 component shows the optimum electrostrictive performance.…”
Section: Resultsmentioning
confidence: 78%
“…Previous research has shown that the reported Q 33 is generally temperature insensitive 60–62 . Huang et al., on the other hand, recently demonstrated a strong temperature‐dependent characteristic of Q 33 in PMN– x PT ceramics with the temperature around the critical region 22 . In this PMN– x PZT system, the Q 33 value of all samples exhibits a modest upward trend as temperature rises, which could be attributed to phase transition and domain reorientation reducing the Q 33 at low temperatures, whereas the Q 33 value at high temperatures is considerably closer to the intrinsic value.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We employed the Curie–Weiss law to characterize the degree of relaxation reflected in the ε r – T spectrum of the crystals , 1 ε normalr = T T C C where C is the Curie constant. Figure shows the fitting results, with ε r starting to conform to the Curie–Weiss law at Burns temperature T B .…”
Section: Resultsmentioning
confidence: 99%